KESEDARAN MUZIUM BARU DI MALAYSIA - Abd Jalal, Ahmad Farid; Yusuf, Abdullah; Abd Hamid, Ahmad Faisal; Abd Rahim, Rahimin Affandi (JURNAL MELAYU SEDUNIA, 2019)
This article will analyze the impact of a new museum in Malaysia. Such a concept occurs in post-independent Malaysia as a response to the fault of the post colonial British museum. This work will utilize the historical method of the primary work done by the colonial scholar in Malaya. It also will utilize contemporary work in the museum in Malaysia. The work finds that several positive developments had happened in the Malaysian museum, which included the critical analysis of the past museum artifacts as well as the use of museums to facilitate the historical subject in the Malaysian education system.